FEATURES OF SUNFLOWER SEEDINGS PRODUCTIVITY FORMATION - Гарбар, Л. А.; Горбатюк, Е. М. (Scientific Progress & Innovations, 2017)
There are the results of the investigations which were aimed to study the influence of sowing terms and row spacing on the formation productivity of different sunflower hybrids. The investigations were conducted during 2014–2016 in conditions of Steppe of Ukraine on typical black low-humus soil. The results of our studies revealed that PR64F50, PR64A15 hybrids provides formation of high yields of sunflower at level of 2,7 t/ha within recommended terms for sowing (by heating the soil to a depth of 10 cm till 10–12 °C) and 35 cm row spacing on typical black low-humus soil of Steppe zone of Ukraine.